The Importance of Pedagogical Reflection in The Professional Skills of A Teacher - Mr. Shukurullo K. Rayimov (Open Academia, 2023)
The Article Analyzes The Professionalism Of The Teacher And The Role Of Pedagogical Reflection In It. There Is Also Provided Information Regarding Types Of Pedagogical Reflection And Its Role In The Pedagogical Activity Development. The Authors Suggestions For The Discussed Problem Are Given
Keywords: Reflection; Professional Reflection; Communicative Reflection